THE CORELLATIONS MOBILE LEGEND GAMES BETWEEN SEX BEHAVIOR IN JUNIOR HIGH SCHOOL 10 REMPANGA VILLAGE - Yuliani winarti; Anita Wahyuni; Nur Ainun Jariah; Rahmat Hidayat (Universitas Muhammadiyah Kalimantan Timur, 2021)
Mobile Legend is a game program that is connected through a network and can be played at anytime and anywhere. It is also can be played in groups around the world. Mobile Legend Game itself has one of the deviations committed by teenagers due to addiction to online games, among others was to say something dirty, being rude, and lazy behavior. From this game, there are several figures (YouTuber) who play this game with open clothes that are sexually tricky. Because of the frequency of watching content like this, teenagers have been unconsciously exposed to pornography which if they already addicted to pornography, can trigger their behavior leading to free sex. The purpose of this study was to determine the connection between playing the mobile legends game to free sex behavior in the teenager. This research was conducted using quantitative methods with a cross-sectional research design. The population of the study was 207 respondents and the sample size taken was 133 people. The sampling technique is a total sampling. From the test, the researchers found that the connection between online games with free sex behavior based on the results of the Chi-Square Test shows a p-value of 0.001 (p <value = 0.05) which means there is a specific connection between playing online game with their free sex behavior in teenager at 10 Middle School on Rempanga village.